2010
DOI: 10.1038/ng.565
|View full text |Cite|
|
Sign up to set email alerts
|

Genome-wide association study of systemic sclerosis identifies CD247 as a new susceptibility locus

Abstract: Systemic sclerosis (SSc) is an autoimmune disease characterized by fibrosis of the skin and internal organs that leads to profound disability and premature death. To identify novel SSc susceptibility loci we conducted the first genome wide association study (GWAS) in a population of Caucasian ancestry including a total of 2296 SSc patients and 5171 controls. Analysis of 279,621 autosomal single nucleotide polymorphisms (SNPs) followed by replication testing in an independent case-control set of European ancest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
293
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 365 publications
(308 citation statements)
references
References 23 publications
7
293
0
3
Order By: Relevance
“…This is consistent with the findings of a GWAS, which failed to identify an association between PTPN22 C1858T and SSc. 119 MS is a common autoimmune disease that targets the central nervous system. A study of family-based samples showed no association between PTPN22 C1858T and MS. 11 This lack of association was confirmed by a GWAS.…”
Section: Diseases Showing No or Weak Association With Ptpn22mentioning
confidence: 99%
“…This is consistent with the findings of a GWAS, which failed to identify an association between PTPN22 C1858T and SSc. 119 MS is a common autoimmune disease that targets the central nervous system. A study of family-based samples showed no association between PTPN22 C1858T and MS. 11 This lack of association was confirmed by a GWAS.…”
Section: Diseases Showing No or Weak Association With Ptpn22mentioning
confidence: 99%
“…Although how the TLR4 signaling pathway contributes to SSc pathogenesis remains enigmatic, it is interesting that several independent case-control and genome-wide association studies identify IFN regulatory factor 5 (IRF5), a member of the IFN regulatory factor (IRF) family, as an SSc susceptibility gene (10)(11)(12)(13)(14)(15). IRFs were identified primarily in the research of the type I IFN system and have been shown to have functionally diverse roles in the regulation of the innate and adaptive immune responses (16).…”
mentioning
confidence: 99%
“…The same region had been previously associated with several autoimmune diseases [20][21][22][23][24][25][26][27] . Another MHC locus has been found in the region that includes the HLA-DPA1, BPB1 and DPB2 genes.…”
Section: Antigen Elaboration and Presentationmentioning
confidence: 99%